Response of Dissolved Organic Matter in the Forest Floor of a Temperate Spruce Stand to Increasing Throughfall. Issue 7 (24th June 2014) - Klotzbücher, Thimo; Kaiser, Klaus; Kalbitz, Karsten
Abstract : In temperate spruce forests, dissolved organic matter (DOM) from forest floors is the major source of organic matter entering the mineral soil and thus it determines important soil properties and element cycling through the ecosystem. We examined effects of doubling locally collected throughfall for 6 yr on the concentrations of dissolved organic C (DOC) and properties of DOM (aromaticity, degree of molecule complexity) in the forest floor. Forest floor solutions below the Oi, Oe, and Oa horizons were sampled every 2 to 4 wk using tension lysimeters. For the controls, the average DOC concentrations in 2002 to 2007 were 43.8 ± 2.6 mg L −1 below the Oi, 49.6 ± 2.7 mg L −1 below the Oe, and 61.0 ± 2.0 mg L −1 below the Oa horizon. Doubling throughfall resulted in average DOC concentrations of 37.4 ± 1.8 mg L −1 (Oi), 49.3 ± 1.6 mg L −1 (Oe), and 50.1 ± 8.0 mg L −1 (Oa). The decreases in concentrations due to throughfall addition as well as the effects on DOM properties were, however, not statistically significant. It is commonly assumed that throughfall inputs are linearly related to water fluxes within and from the forest floor. Under that assumption, the results suggest that DOM fluxes are controlled by water fluxes rather than by the quantity of C that can be mobilized from the soil organic matter. Hence, increasing precipitation due to future climate changes presumably will result in enhanced DOM fluxes into the mineral horizons.